Odwołania do Aleksandra Wielkiego i ich rola w Żywocie Demetriusza Plutarcha z Cheronei - Zieliński, Tomasz (Collectanea Philologica, 2020)
Among all Plutarch’s Lives of men that lived after IV B.C., the biography of Demetrius Poliorcetes contains the most references to Alexander the Great. It is noteworthy that references to this figure in comparison to other Plutarchean biographies occur in greater numbers and in various contexts. The article is an attempt to demonstrate that the references to Alexander the Great played an important role in the construction of the Plutarch’s Life of Demetrius. Thus their purpose was to portrayal Poliorcetes as a failed imitator of famous Macedonian king. The considerations presented in the article can be used as an argument for changing the image of Demetrius in scholarly literature.